Developing new chemical–rheological models and chemical–durability indices of bitumen - Hermadi, Madi (2013)
Significant correlation among chemical properties, rheological characteristics and durability of bitumen is very important in evaluating and modifying bitumen. However, a number of previous studies found inconsistent correlation. Therefore, a study on developing new chemical-rheological models and chemical-durability indices was carried out. Two bitumen fractionation method, Rostler and Corbett methods were used to extract each chemical fraction of bitumen. A number of experiments were conducted to evaluate the effect of each chemical fraction on bitumen rheology such as the effect of asphaltenes, polar aromatics, naphthene aromatics, nitrogen bases, first acidaffins, second acidaffins and paraffins on elastic modulus (G’), viscous modulus (G”) or fatigue factor (G*sin[δ]), and rutting fator (G*/sin[δ]). Two bitumen from different sources, namely Petronas petroleum bitumen and Buton rock asphalt (BRA) bitumen, were used. New chemicalrheological models were formulated to estimate the bitumen rheology in corporating parameters which are G’, G” or (G*sin[δ]), and (G*/sin[δ]) based on the chemical properties. Furthermore, new chemical durability indices that may indicate the ageing rate of bitumen during short-term and long-term ageing were also formulated. Based on statistical analyses, the models and the indices, which were developed by using chemical properties according to Rostler method were found to be invalid because the real and the predicted rheology were significantly different. While according to Corbett method the models and the indices were valid because the differences is not significant since t-score of the models and the indices were maximum 2.679 and 2.119 or less than t-critical 2.797 and 2.861 respectively). The novelties of this study are the new models and the new indices can be used to predict the bitumen rheology and ageing rate based on the chemical composition. Furthermore, they are very important as guides in modifying a bitumen chemical composition to produce a bitumen mixture with the desired rheology and short-term or long-term ageing rate